Cultural Crossroads in the Corinthian Gulf during the EBA: Insights into a Ceramic Assemblage from Aigion - Michalopoulos, Panagiotis (Archäologischer Anzeiger, 2024)
The Corinthian Gulf offers valuable information with regard to the effort to understand the cultural interactions of the late 3ʳᵈ millennium when major changes occurred in southern mainland Greece, including Eastern Achaea (Aigialeia). To this end, the settlement of Aigion is particularly important because of its positioning and the special features of its pottery, illustrated by the ceramic assemblage from the Minasian plot. Despite limitations, this assemblage provides significant evidence of the local ceramic tradition, the associated changes and the chronological synchronisms and possible interactions with other sites. Based on this evidence an attempt to associate Aigion with a network of settlements around the Corinthian Gulf sheds some light on its role in an interconnected environment, within which a large part of the contemporary transformations in the Aegean took place.